Incomplete vaccination coverage in European children with end-stage kidney disease prior to renal transplantation - Höcker, Britta; Schnitzler, Paul; Rieger, Susanne; Krupka, Kai; Bruckner, Thomas; Fichtner, Alexander; Tönshoff, Burkhard (Pediatric nephrology, 2018)
Background: Because infections constitute a major cause of morbidity and mortality in paediatric renal allograft recipients, avoidance of preventable systemic infections by vaccination before transplantation is of utmost importance. However, data on the completeness of vaccinations and factors associated with incomplete vaccination coverage are scarce. Methods: Within the framework of the Cooperative European Paediatric Renal Transplant Initiative (CERTAIN), we therefore performed a multi-centre, multi-national, retrospective study investigating the vaccination coverage before transplantation of 254 European children with end-stage renal disease (mean age 10.0 ± 5.6 years). Results: Only 22 out of 254 patients (8.7%) presented complete vaccination coverage. In particular, the respective vaccination coverage against human papillomavirus (27.3%), pneumococci (42.0%), and meningococci (47.9%) was low. Patients with complete pneumococcal vaccination coverage had numerically less lower respiratory tract infections during the first 3 years post-transplant than children without vaccination or with an incomplete status (16.4% vs 27.7%, p = 0.081). Vaccine-preventable diseases post-transplant were 4.0 times more frequently in unvaccinated than in vaccinated patients. Factors associated with an incomplete vaccination coverage were non-Caucasian ethnicity (OR 9.21, p = 0.004), chronic dialysis treatment before transplantation (OR 6.18, p = 0.001), and older age at transplantation (OR 1.33, p < 0.001). Conclusions: The vaccination coverage in paediatric kidney transplant candidates is incomplete. Paediatric nephrologists, together with primary-care staff and patients’ families, should therefore make every effort to improve vaccination rates before kidney transplantation.
First online: 05 October 2017
Gesehen am 13.07.2018